An observational study of functional abilities in infants, children, and adults with type 1 SMA. (21st August 2018) - Pane, Marika; Palermo, Concetta; Messina, Sonia; Sansone, Valeria A.; Bruno, Claudio; Catteruccia, Michela; Sframeli, Maria; Albamonte, Emilio; Pedemonte, Marina; D'Amico, Adele; Brigati, Giorgia; de Sanctis, Roberto; et al.
Abstract : Objective: To report cross-sectional clinical findings in a large cohort of patients affected by type 1 spinal muscular atrophy. Methods: We included 122 patients, of age ranging between 3 months and 22 years, 1 month. More than 70% (85/122) were older than 2 years and 25% (31/122) older than 10 years. Patients were classified according to the severity of phenotype and to the number of SMN2 copies. Results: Patients with the more common and the most severe phenotype older than 2 years were, with few exceptions, on noninvasive ventilation and, with increasing age, more often had tracheostomy or >16-hour ventilation and a gastrostomy inserted. In contrast, 25 of the 28 patients with the mildest phenotype older than 2 years had no need for tracheostomy or other ventilatory or nutritional support. In patients older than 2 years, the Children's Hospital of Philadelphia Infant Test of Neuromuscular Disorders scores were generally lower compared to those found in younger patients and showed distinct levels of functional abilities according to the severity of the phenotype. Similar findings were also observed on the Hammersmith Infant Neurological Examination. Conclusions: Our findings confirm that, after the age of 2 years, patients with type 1 spinal muscular atrophy generally survive only if they have gastrostomy and tracheostomy or noninvasive ventilation >16 hours and have low scores on the functional scales. More variability, however, can be expected in those with the mildest phenotype, who achieve head control. These data provide important baseline information at the time treatments are becoming available.